DESIGN COURSE PROGRAM "BLENDED LEARNING" - Kukharenko , V. (Journal of Information Technologies in Education (ITE), 2017)
The paper describes the main features of mixed teaching: the tasks of mixed learning, learning models, micro-training, video fragments, the new role of the teacher. To create a distance training course for teachers and university lecturers, an open three-week dialectical distance course was conducted. The peculiarities of the connektivist approach and the high level of the trainees allowed to determine the key components of the course "Mixed training". Tendencies in the development of education in the world, the role of mixed learning, gaming, analyzed SWOT analysis for mixed learning. The problematic issues in the conductivity of remote sensing courses have been clarified. To test the formed hypotheses, a six-week pilot distance course was created, which included the most important sections: the formation of the goal of the class, the model of the inverted class, tools for mixed instruction, the organization of the learning process and the evaluation of learning outcomes. The educational process was conducted for all comers. The course was signed by 218 students, the number of teachers and university teachers was approximately the same. Active listeners were 48, successfully completed the course - 18 listeners. The results of the training and the interviews of the listeners make it possible to create a distance course "Mixed training" for the professional development of teachers and teachers of higher educational institutions.